Discrepancies Between Legal Norms and the Practice of Appointing ‘Wali Hakim’ for Legally Recognized Children at Medan Tembung Religious Affairs Office - Rahmat Hakim Harahap; Zainal Arifin Purba (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This study investigates the legal foundations and challenges surrounding the appointment of a judge guardian (wali hakim) in the marriage of children deemed legitimate under the Compilation of Islamic Law (KHI), with a particular focus on cases involving children born from adulterous relationships. Employing a juridical-normative methodology, the research combines literature review and regulatory content analysis with empirical data obtained through interviews to assess implementation at the Office of Religious Affairs (KUA). The findings reveal interpretive ambiguities in Articles 99 and 100 of the KHI, which have led to discretionary practices by KUA officials who appoint judge guardians even when the child fulfills the legal criteria of legitimacy. This inconsistency between normative law and administrative application results in legal uncertainty and underscores the need for regulatory reform concerning guardianship in cases involving children of illicit conception. The study contributes to the scholarly discourse by critically analyzing these legal gaps and proposing measures to reinforce legal certainty and civil protections for children in marriage. It advocates for a reformulation of KHI norms grounded in the principle of maslahah to ensure justice, clarity, and the protection of children’s rights in Islamic family law practices.